Upaya Pencegahan Dan Penanganan Kekerasan Seksual Di Perguruan Tinggi (PETITUM, 2022)
ABSTRACT: The increasing increase in sexual violence occurring in higher education institutions will directly or indirectly result in less than optimal implementation of the Tridharma of Higher Education and reduce the quality of higher education, so that to prevent and handle sexual violence, regulations are needed that guarantee legal certainty. With the Minister of Education and Culture Regulation Number 30 of 2021 which aims to protect students from sexual violence. The condition of zero tolerance for sexual violence on campus, which was initiated by the Minister of Education and Culture, is eagerly awaited. Through legal outreach regarding "Regulation of the Minister of Education, Culture, Research and Technology Number 30 of 2021 concerning Prevention and Handling of Sexual Violence in Higher Education Environments", as a form of providing and increasing understanding regarding the Prevention and Handling of Sexual Violence in Higher Education Environments. Higher education institutions are responsible for carrying out efforts to prevent and handle sexual violence independently, free from influence or pressure from any party, while the method for preventing and handling sexual violence is through learning; strengthening governance; and strengthening the culture of the Student, Educator and Education Personnel community.ABSTRAK: Semakin meningkatnya kekerasan seksual yang terjadi di perguruan inggi secara langsung atau tidak langsung akan berdampak pada kurang optimalnya penyelenggaraan Tridharma Perguruan Tinggi dan menurunkan kualitas pendidikan tinggi, sehingga untuk mencegah dan menangani kekerasan seksual tersebut, perlu pengaturan yang menjamin kepastian hukum. Dengan adanya Permendikbud Nomor 30 Tahun 2021 yang bertujuan melindungi para mahasiswa dari kekerasan seksual. Kondisi zero tolerance kekerasan seksual di kampus, yang digagas permendikbud ini sangat ditunggu. Melalui penyuluhan hukum mengenai “Peraturan Menteri Pendidikan, Kebudayaan, Riset, dan Teknologi Nomor 30 Tahun 2021 tentang Pencegahan dan Penanganan Kekerasan Seksual di Lingkungan Perguruan Tinggi”, sebagai bentuk pemberian dan peningkatan pemahaman mengenai pencegahan dan penanganan kekerasan seksual di LingkunSgan Perguruan Tinggi. Perguruan Tinggi bertanggungjawab melaksanakan upaya pencegahan dan penanganan kekerasan seksual secara independen, bebas dari pengaruh maupun tekanan dari pihak manapun, sedangkan metode pencegahan dan penaganannya melalui pembelajaran; penguatantata kelola; dan penguatan budaya komunitas Mahasiswa, Pendidik, dan Tenaga Kependidikan.